1997
DOI: 10.1074/jbc.272.1.345
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate Differentially Regulates Elastin and Collagen Biosynthesis in Vascular Smooth Muscle Cells and Skin Fibroblasts by Pretranslational Mechanisms

Abstract: Ascorbate contributes to several metabolic processes including efficient hydroxylation of hydroxyproline in elastin, collagen, and proteins with collagenous domains, yet hydroxyproline in elastin has no known function. Prolyl hydroxylation is essential for efficient collagen production; in contrast, ascorbate has been shown to decrease elastin accumulation in vitro and to alter morphology of elastic tissues in vivo. Ascorbate doses that maximally stimulated collagen production (10-200 microM) antagonized elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 65 publications
1
100
0
1
Order By: Relevance
“…5A). Ascorbic acid treatment increases collagen production and was used as a positive control (36,(47)(48)(49). Furthermore, there was no increase in type I collagen in the detergent-insoluble ECM when CRT Ϫ/Ϫ MEFs were treated with exogenous CRT (Fig.…”
Section: ϫ/ϫmentioning
confidence: 99%
See 1 more Smart Citation
“…5A). Ascorbic acid treatment increases collagen production and was used as a positive control (36,(47)(48)(49). Furthermore, there was no increase in type I collagen in the detergent-insoluble ECM when CRT Ϫ/Ϫ MEFs were treated with exogenous CRT (Fig.…”
Section: ϫ/ϫmentioning
confidence: 99%
“…Ascorbic Acid Stimulates Collagen Trafficking and Deposition in CRT-deficient Cells-Ascorbic acid increases collagen transcript stabilization and is a cofactor for proline hydroxylation of procollagen, which enhances translation efficiency and secretion (36,(47)(48)(49). Because CRT Ϫ/Ϫ MEFs have apparent defects in post-translational processing of type I collagen, we investigated whether ascorbic acid can rescue these defects in the CRT Ϫ/Ϫ MEFs.…”
Section: Crt Plays a Role In Type I Collagen Retention In The Er And mentioning
confidence: 99%
“…Of note, opposing trends in collagen and elastic matrix generation were observed in this study and in others. 42,82,88 Despite increased elastic matrix deposition on the 3D electrospun PCL scaffolds described above, compared to 2D tissue culture plastic, no corresponding differences were noted in the mRNA expression of matrix proteins. This suggests that substrate chemistry, surface topography, and surface compliance (i.e., the ability to be deformed) can in certain cases influence post-transcriptional mechanisms of tropoelastin recruitment and crosslinking without impacting elastin gene expression itself.…”
Section: D Versus 3d Substratesmentioning
confidence: 97%
“…This signaling leads to physiological outcomes such as enhanced or inhibited elastic matrix synthesis. Prior studies have shown that elastin matrix synthesis is regulated by numerous biochemical factors that may be broadly classified as elastin synthesis inhibitors (e.g., ascorbic acid, 42 basic fibroblast growth factor 43 , cyclic AMP 44 , and monensin 45 ) and elastin synthesis stimulators (e.g., cyclic GMP, 44 fetal calf serum, 46 insulin-like growth factor 1 [IGF-1], 47,48 and transforming growth factor b1 [TGFb1]…”
Section: Elastin In Vascular Tissue Engineering 205 Elastogenic Stimumentioning
confidence: 99%
“…It is necessary for VSMC collagen synthesis, since without it (Schwartz et al, 1982), or in the presence of the non-functional ascorbate analog ethyl-3,4-dihydroxybenzoate (Sasaki et al, 1987), VSMCs form little collagen. In addition to enhancing post-translational collagen modification in VSMCs, ascorbate also increases procollagen synthesis by a pre-translational mechanism (Barone et al, 1985;Davidson et al, 1997). Although collagen synthesis is required for VSMC migration and proliferation (Ivanov et al, 1997;Rocnik et al, 1998), the overall effect of ascorbate on these processes seems to be the opposite.…”
Section: Vascular Smooth Muscle Cellsmentioning
confidence: 99%